Modified Natural Zeolites as Sorbents for Separation and Preconcentration of Traces Amount of Metal Ions - JAMSHIDI, RASOOL; AFZALI, ZAHRA; AFZALI, KAVOOS (Asian Journal of Chemistry, 2010)
This work assesses the potentialities of natural zeolites as useful adsorptive material for separation and preconcentration of trace amounts of metal ions. Natural analcime and natrolite zeolites were modified by benzyldimethyltetradecylamonium chloride solution at 110 ºC for 12 h and then was saturated with 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (5-Br-PADAP) as useful reagent for preconcentration of trace metal ions. A column contains modified zeolite as useful adsorbent was used for solid-phase extraction of trace lead and cadmium ions. Different parameters that necessary for solid-phase extraction were examined in this work and zeolites were known useful adsorbents for solid-phase extraction and preconcentration of traces metal ions.